Surface modelling of vehicle frontends for pedestrian safety with the FlexPLI. Issue 3 (4th May 2017) - Mößner, S.; Rudolph, T.; Duddeck, F.
ABSTRACT: Structural design of vehicle frontends needs to satisfy high requirements for pedestrian safety. A method to derive a simplified vehicle model is proposed, enabling quick investigations to identify trends to reduce injury values of the Flexible Pedestrian Leg Impactor (FlexPLI). Derived from an initial simulation of the original full-scale finite element (FE) model, the simplification is based on the computed non-linear stiffness of the frontend's surface. The method is illustrated via a very small principal example and investigated further for three different kinds of more complex modelling. In addition, a procedure to automate the model generation is shown. Even though the impactor is not simplified, the simulation time of the leg impact is reduced by a factor of ten in contrast to that of the original model. A comparison, full model against reduced model, of the impactor's kinematics shows the high validity of the approach. An application example demonstrates the approach's ability to predict trends and sensitivities with minimised manual and computational effort, which is necessary in the early development phase to investigate a wider range of design options.